Fault localization using function call frequencies - Vancsics Béla; Horváth Ferenc; Szatmári Attila; Beszédes Árpád (2022)
In traditional Spectrum-Based Fault Localization (SBFL), hit-based spectrum is used to estimate a program element's suspiciousness to contain a fault, i.e., only the binary information is used if the code element was executed by the test case or not. Count-based spectra can potentially improve the localization effectiveness due to the number of executions also being available. In this work, we use function-level granularity and define count-based spectra which use function call frequencies. We investigate the naive approach, which simply counts the function call instances. We also define a novel method which is based on counting the different function call contexts, i.e., the frequency of the investigated function occurring in unique call stack instances during test execution. The basic intuition is that if a function is called in many different contexts during a failing test case, it will be more probable to be accountable for the fault. We empirically evaluated the fault localization capability of different variations of the approach and compared them to 9 traditional SBFL techniques using the Defects4J benchmark. We show that: (i) naive counts result in worse rank positions than the hit-based approach, but (ii) unique counts produce better rank positions with some of the algorithm variants.
Keywords: Számítás- és információtudomány